2003
DOI: 10.1289/ehp.5494
|View full text |Cite
|
Sign up to set email alerts
|

Large effects from small exposures. I. Mechanisms for endocrine-disrupting chemicals with estrogenic activity.

Abstract: During the past decade a number of pesticides, industrial by-products, manufactured products such as plastics, and natural chemicals have been shown to disrupt the endocrine system. These chemicals are referred to as endocrine-disrupting chemicals (EDCs). These chemicals have received considerable attention, in part because endocrine disruption is a relatively unstudied area in toxicology and is only recently being taken into account in risk assessment. The focus here is on EDCs with estrogenic activity (EEDCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
489
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 805 publications
(514 citation statements)
references
References 128 publications
16
489
1
8
Order By: Relevance
“…1) The developmental (fetal) basis of adult disease: The developing fetus or infant is much more sensitive to endocrine-disrupting compounds than the adult; moreover, effects early in life may not be manifested until adulthood [63]. 2) Extremely low-dose exposures may exert significant effects on a developing organism, particularly if the exposure occurs during critical developmental periods [165,140,15,91]. Furthermore, effects are often manifested via non-traditional dose-response curves, similar to actions of steroid and nuclear receptor hormones [165,63].…”
Section: Endocrine Disruption and Developing Neuroendocrine Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The developmental (fetal) basis of adult disease: The developing fetus or infant is much more sensitive to endocrine-disrupting compounds than the adult; moreover, effects early in life may not be manifested until adulthood [63]. 2) Extremely low-dose exposures may exert significant effects on a developing organism, particularly if the exposure occurs during critical developmental periods [165,140,15,91]. Furthermore, effects are often manifested via non-traditional dose-response curves, similar to actions of steroid and nuclear receptor hormones [165,63].…”
Section: Endocrine Disruption and Developing Neuroendocrine Systemsmentioning
confidence: 99%
“…2) Extremely low-dose exposures may exert significant effects on a developing organism, particularly if the exposure occurs during critical developmental periods [165,140,15,91]. Furthermore, effects are often manifested via non-traditional dose-response curves, similar to actions of steroid and nuclear receptor hormones [165,63]. 3) Environmental exposures generally occur in complex mixtures, as a contaminated environment is rarely affected by a single toxicant, and the effects may occur by more than one mechanism [15].…”
Section: Endocrine Disruption and Developing Neuroendocrine Systemsmentioning
confidence: 99%
“…The U.S. EPA established a reference dose (RfD) for humans at 50 µg BPA/kg body weight (BW) day –1 based on a 1000‐fold reduction of the lowest observed adverse effect level (LOAEL) of 50 mg kg –1 BW day –1 15, 16. Some studies have indicated that the daily human intake of BPA is less than 1 µg kg –1 BW day –1 , rendering the RfD to be considered safe to humans 17.…”
Section: Introductionmentioning
confidence: 99%
“…However, the RfD for BPA (50 µg/kg/day) was calculated using the lowest observable adverse effect level (LOAEL) and 1,000-fold safety factors because a NOAEL had not been determined (Welshons et al 2003). More than 150 published studies describe BPA effects in animals exposed to < 50 mg/kg/day, including altered development of the male and female reproductive tracts, organization of sexually dimorphic circuits in the hypothalamus, onset of estrus cyclicity and earlier puberty, altered body weight, altered organization of the mammary gland, and cancers of the mammary gland and prostate; > 40 of these studies examined doses less than the RfD (Richter et al 2007).…”
mentioning
confidence: 99%